Remarks on Two Recent Results About Polynomials With Prescribed Zeros - Qazi, M. A. (Sarajevo Journal of Mathematics, 2024)
We make some observations about the results contained in a paper published in this journal in the year 2011. 2010 Mathematics Subject Classification. 30A10, 30C10, 30C15.